Elementary School Teacher Competency Development in Creating Digital Learning Media Anchor App Based - Non Dwishiera Cahya Anasta; Mela Darmayanti; Ani Hendriani (Universitas Pendidikan Indonesia (UPI), 2021)
The industrial revolution that is happening in this era requires teachers to always and constantly adapt to technological developments. The use of ICT in learning activities has an important role, especially during the current COVID-19 pandemic. The condition of distance learning creates problems for teachers. The lack of teacher skills in developing digital learning media makes teachers less innovative in making learning media. Even though there are currently many online-based applications that provide various features that can be used to create interesting learning media. Online learning media is a learning media that is in accordance with the characteristics of the current digital generation. For this reason, teachers need to equip themselves with digital literacy skills. This study aims to develop the ability of elementary school teachers to innovate in creating Anchor application-based learning media. The research design used is action research. Participants consisted of 100 teachers from districts and cities in West Java, teachers from DKI Jakarta, and the City of Yogyakarta, Indonesia. The results show that the teacher is able to complete the task of making anchor application-based learning media. This shows that they are able to develop their digital literacy skills in learning. Teachers can easily create learning media in the form of podcasts, using the anchor application. It can be concluded that structured and controlled training and mentoring can develop the skills and innovations of elementary school teachers in creating digital learning media. The research design used is action research. Participants consisted of 100 teachers from districts and cities in West Java, teachers from DKI Jakarta, and the City of Yogyakarta, Indonesia. The results show that the teacher is able to complete the task of making anchor application-based learning media. This shows that they are able to develop their digital literacy skills in learning. Teachers can easily create learning media in the form of podcasts, using the anchor application. It can be concluded that structured and controlled training and mentoring can develop the skills and innovations of elementary school teachers in creating digital learning media. The research design used is action research. Participants consisted of 100 teachers from districts and cities in West Java, teachers from DKI Jakarta, and the City of Yogyakarta, Indonesia. The results show that the teacher is able to complete the task of making anchor application-based learning media. This shows that they are able to develop their digital literacy skills in learning. Teachers can easily create learning media in the form of podcasts, using the anchor application. It can be concluded that structured and controlled training and mentoring can develop the skills and innovations of elementary school teachers in creating digital learning media. The results show that the teacher is able to complete the task of making anchor application-based learning media. This shows that they are able to develop their digital literacy skills in learning. Teachers can easily create learning media in the form of podcasts, using the anchor application. It can be concluded that structured and controlled training and mentoring can develop the skills and innovations of elementary school teachers in creating digital learning media. The results show that the teacher is able to complete the task of making anchor application-based learning media. This shows that they are able to develop their digital literacy skills in learning. Teachers can easily create learning media in the form of podcasts, using the anchor application. It can be concluded that structured and controlled training and mentoring can develop the skills and innovations of elementary school teachers in creating digital learning media.